Environmental Variation and How its Spatial Structure Influences the Cross-Shelf Distribution of High-Latitude Coral Communities in South Africa - Porter, Sean N.; Schleyer, Michael H. (Diversity (Basel), 2019)
Coral communities display spatial patterns. These patterns can manifest along a coastline as well as across the continental shelf due to ecological interactions and environmental gradients. Several abiotic surrogates for environmental variables are hypothesised to structure high-latitude coral communities in South Africa along and across its narrow shelf and were investigated using a correlative approach that considered spatial autocorrelation. Surveys of sessile communities were conducted on 17 reefs and related to depth, distance to high tide, distance to the continental shelf edge and to submarine canyons. All four environmental variables were found to correlate significantly with community composition, even after the effects of space were removed. The environmental variables accounted for 13% of the variation in communities; 77% of this variation was spatially structured. Spatially structured environmental variation unrelated to the environmental variables accounted for 39% of the community variation. The Northern Reef Complex appears to be less affected by oceanic factors and may undergo less temperature variability than the Central and Southern Complexes; the first is mentioned because it had the lowest canyon effect and was furthest from the continental shelf, whilst the latter complexes had the highest canyon effects and were closest to the shelf edge. These characteristics may be responsible for the spatial differences in the coral communities.